Case Report: Successful endoscopic full-thickness resection of an irregular submucosal tumor of the esophagus with surface focal white patches: horseshoe-shaped leiomyoma - Pan, Lili; Wang, Chuanfang; Zhang, Chong; Fan, Lijuan; Ma, Ran (Frontiers in Oncology, 2025)
Esophageal leiomyoma is a rare benign tumor of the esophagus, accounting for approximately 1.2% of all esophageal tumors. Endoscopically, it typically appears as a protrusion into the esophageal lumen with intact and smooth mucosa, which can be slightly moved with biopsy forceps and rarely causes luminal stenosis. The current case presents an irregular submucosal esophageal mass with localized white patches on the surface—an endoscopic appearance not previously reported. These surface white patches complicated the diagnosis, and the postoperative pathological finding of a horseshoe-shaped leiomyoma is even more unusual. Preoperative imaging with chest and abdominal CT and endoscopic ultrasound identified the lesion in the muscularis propria, and successful endoscopic full-thickness resection was performed. This minimally invasive approach was confirmed by pathology to be precise, safe, and effective, achieving treatment outcomes comparable to traditional surgical resection.